Uwarunkowania psychologiczno-społeczne przepowiadania słowa Bożego - Biela, Bogdan (Studia Pastoralne, 2026)
God speaks to a man and at the same time speaks to him through the other person. We are, therefore, within the realm of interpersonal relations. Hence while talking about preaching the Word of God one has to pay attention to circumstances and rules of interaction of the preached Word of God on a listener’s reason, will and emotions as major receptors of the content of the church preaching and at the same time as factors of the act of a personal faith. Such a preaching of the Word of God results from its purpose, securing both the personalistic and ecclesiastical character of the preaching. Therefore in the preaching of the Word of God a vital role is performed by a social community. Experience shows that even a solid intellectual and religious formation does not suffice for a proper shaping of the attitude of faith, if one does not have a proper support in an environment of one’s life. Hence the preaching cannot escape sociological conditions and be restricted only to transmitting an orthodox Christian teaching. Preaching the Gospel in the community of the faithful should be supported and intensified by a communal experience of this church community of faith.